Medicine, Religion, and the Humanitarian Ethos: Walter B. Cannon, Unitarianism, and the Care of Spanish Republican Refugees in France. (21st April 2022) - Arrizabalaga, Jon; Martínez-Vidal, Àlvar
Abstract: Biographies of Walter B. Cannon (1871-1945) usually present two sides of his life: one, where he was an outstanding man of science in the United States during the so-called "Golden Age of Medicine, " and the other, where he was a leading humanitarian activist engaged in myriad causes, notably in the defense of Spanish democracy during the Civil War (1936-1939). However, these biographies fail to take into account that the apparent link between these two sides of his life was his religious conviction. This study summarizes the aims and accomplishments of the American Medical Bureau to Aid the Spanish Democracy (AMBASD) of which Cannon was chair between 1937 and 1939. Then, it examines Cannon's inspirational role on the international relief work with Spanish Republican refugees in France, through the case of the Varsovie Hospital of Toulouse that between 1945 and 1949 was jointly managed by the Unitarian Service Committee (USC) and the Joint Anti-Fascist Refugee Committee (JAFRC), and renamed Varsovie Hospital/Walter B. Cannon Memorial in recognition of the Spanish Republicans' debt for his extraordinary contribution during the Spanish Civil War and beyond. Finally, the article investigates the Unitarian roots of Cannon's humanitarian ethos by exploring the historical relations of this religious movement with science and with many major actors at Harvard University as well as the links of Cannon's relatives to Unitarianism. The analysis reveals Unitarianism's influence on Cannon's views about science, democracy, and liberty, as well as on his remarkable involvement in the medical solidarity movement with the Second Spanish Republic and other similar commitments. In sum, it shows how important is to branch out in our studies of medical and scientific practice to include practitioners' broader social and religious communities in order to understand their motivations, achievements, and behavior.